Locoregional blockage of the transverse abdominal plane in a female cat who underwent ovariohysterectomy and cystotomy: Case report - TELES MARTINS, LUDIMILLA CRISTINA TELES MARTINS; Oliveira, Flávia; HOLZLSAUER, Guilherme; Gering, Ana Paula (Pubvet, 2021)
Blockade of the transverse abdominal plane (Tap Block) is a technique of locoregional anesthesia that consists of the application of local anesthetic in the interneurofascial plane, promoting blockage of the skin, muscles and parietal peritoneum of the ventral abdominal wall in animals. The aim of the study was to report the use of transverse abdominal plane block in a cat submitted to ovariohysterectomy and cystotomy. A cat was attended at the Veterinary University for pre-surgical castration care. The tutor reported that he was applying an anti-heat vaccine and has since observed an increase in abdominal volume. Laboratory blood tests, biochemical tests (Alanine Amino Trasnferase-ALT, alkaline phosphatase, urea and creatinine), total proteins and fractions and abdominal ultrasound were performed, in which a calculation was observed in the urinary vesicle and pyometra/hemometra/mucometra. The patient was referred for therapeutic ovariohysterectomy and cystotomy. Pre-anesthetic medication consisted of midazolam (0.2 mg/kg), ketamine (2 mg/kg), methadone (0.3 mg/kg) and acepromazine (0.03 mg/kg) all intramuscularly. Twenty minutes after MPA, the 22G catheter was inserted into the right cephalic vein and then the animal was sent to the ultrasound room to perform the locoregional block. The animal was placed in the supine position and ultrasound-guided locoregional anesthesia of the transverse plane of the abdomen was performed with bupivacaine (0.2 ml/kg) diluted 1: 2 in water for injection distributed in four points of the abdomen. In the operating room, anesthetic induction was performed with propofol dose effect and for the maintenance of anesthesia, sevofluorane was chosen. During anesthetic monitoring, hemodynamic changes that revealed nociception in the animal were not observed, due to the use of locoregional block. Recovery took place quickly, with no signs of pain in animal behavior, showing the analgesic efficacy of the block and the importance of it in the anesthetic routine.